2017
DOI: 10.5897/jene2017.0625
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of farmers perception towards soil and water conservation in Obi Koji Peasant Association, Woliso District, South West Shewa Ethiopia

Abstract: The severity of erosion is one of the major factors which calls for various efforts to reduce unsustainable agricultural productivity. But the efforts were fails because of some factors like need of incentives, technology that needs too much labor, reduction of farm size and lack of awareness. The main purpose of this research was to determine the factors affecting farmer's perception to make decision on soil and water conservation practices on their farm land. A total of 36 (20 male and 16 female) household s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A study in Iran showed that farmers' positive attitude on uptake of watershed practices and acceptance of soil erosion as a major constraint contributed greatly to uptake of the practices (Hosseini et al, 2014). Support from the Government and private organizations motivated development of a positive attitude among farmers to take up soil and water conservation practices leading to enhanced uptake of the practices (Zerssa, Bezabih & Dinkecha, 2017). High rate of uptake for soil and water conservation practices is enhanced by ease of use, low cost and their effectiveness among farmers with positive attitude (Junge, Deji, Abaidoo, Chikoye & Stahr, 2009).…”
Section: Farmers' Attitude On Watershed Management Practices Promoted In the Catchmentsmentioning
confidence: 99%
“…A study in Iran showed that farmers' positive attitude on uptake of watershed practices and acceptance of soil erosion as a major constraint contributed greatly to uptake of the practices (Hosseini et al, 2014). Support from the Government and private organizations motivated development of a positive attitude among farmers to take up soil and water conservation practices leading to enhanced uptake of the practices (Zerssa, Bezabih & Dinkecha, 2017). High rate of uptake for soil and water conservation practices is enhanced by ease of use, low cost and their effectiveness among farmers with positive attitude (Junge, Deji, Abaidoo, Chikoye & Stahr, 2009).…”
Section: Farmers' Attitude On Watershed Management Practices Promoted In the Catchmentsmentioning
confidence: 99%